1997
DOI: 10.5860/crl.58.1.81
|View full text |Cite
|
Sign up to set email alerts
|

A Question of Quality: How Authors and Editors Perceive Library Literature

Abstract: Librarians with faculty status are expected to do research and publish just as their teaching colleagues do. But unlike teaching faculty, most librarians have neither flexible work schedules nor nine-month contracts that are conducive to ongoing research and publication. This means that the requirement to publish in order to be a successful academic often competes with the requirement to perform daily work in order to be a successful librarian. One of the reasons the authors undertook this study was to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
0
5
0
Order By: Relevance
“…21 Barbara Floyd and John Phillips conducted a survey of academic librarians and found that the most consistent worry on the part of librarians was that "the requirement to publish in order to be a successful academic often competes with the requirement to perform daily work in order to be a successful librarian." 22 In addition, librarians consistently responded that they were not provided with sufficient blocks of time to conduct research. Jeanne Brown suggested the use of time logs by librarians in order to allocate small blocks of time each day to do research and that librarians should be assured that "we do have time: not enough to do everything we'd like to do, but time nonetheless to allocate as we see fit.…”
Section: Literature Reviewmentioning
confidence: 99%
“…21 Barbara Floyd and John Phillips conducted a survey of academic librarians and found that the most consistent worry on the part of librarians was that "the requirement to publish in order to be a successful academic often competes with the requirement to perform daily work in order to be a successful librarian." 22 In addition, librarians consistently responded that they were not provided with sufficient blocks of time to conduct research. Jeanne Brown suggested the use of time logs by librarians in order to allocate small blocks of time each day to do research and that librarians should be assured that "we do have time: not enough to do everything we'd like to do, but time nonetheless to allocate as we see fit.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For a number of years scholars have expressed concern about the quality, quantity and impact of LIS research output (Floyd and Phillips, 1997;Gorman, 2000;Michaels, 1993;Robbins, 1991;St Clair, 1993). Some writers have advanced a number of reasons for this situation and made suggestions for its improvement.…”
Section: Introductionmentioning
confidence: 99%
“…8 Barbara L. Floyd and John C. Phillips re ported that publishing was a requirement for tenure for close to 80 percent of the surveyed authors. 9 Others have looked at how evaluation criteria for academic li brarians vary by type of academic insti tution. Using the 1987 Carnegie Classifi cations to distinguish among institutions, Betsy Park and Robert Riggs found that doctoral-granting and comprehensive universities were more likely to require evidence of publication than either re search or liberal arts institutions.…”
Section: Reasonsf Orfpublishingmentioning
confidence: 99%